Kedudukan dan Fungsi Dewan Pengawas Syariah Dalam Internal Auditor Bank Syariah - Try Subakti; Nurhidayah Marsono (STIS DAFA MATARAM, 2021)
The history of banking regulation and supervision in Indonesia cannot be separated from the desire to develop national banking as well as to tackle the accompanying banking crimes. Bank supervision through audits of state banks is carried out in layers by the financial and development supervisory board (BPKP), the financial audit body (BPK), public accounting offices including by the Indonesian bank itself, the sharia supervisory board for Islamic banks.